STUDY ON BERRIER TRAP FISHING TECNOLOGY IN SIAK RIVER WATERS VILLAGE BUNGA RAYA DISTRICT BUNGA RAYA SIAK REGENCY RIAU PROVINCE - akbar, Miptahul; Brown, Arthur; ', Bustari (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research was conducted in May 2015 in the village of Bunga Raya District of Bunga Raya regency of Siak Province of Riau. This study aimed to analyze aspects relating to technological aspects of environmental friendliness and aspects business feasibility. The method used is a survey method. From environmental assessment is was abtained the score 30,5 which mean this technology can classified as a very environmental friendly. The results of the feasibility study were Benefit cost ratio of 1.3 while the financial rate of return of 0,32% and a payback period of 3 years.Keywords: Berrier Trap, Environmental Friendliness, Business Feasbility